Nazism and neo-nazism in film and media - Lee, C. J. P. (Amsterdam University Press, 2018)
This timely book takes an original transnational approach to the theme of Nazism and neo-Nazism in film, media, and popular culture, with examples drawn from mainland Europe, the UK, North and Latin America, Asia, and beyond. This approach fits with the established dominance of global multimedia formats, and will be useful for students, scholars, and researchers in all forms of film and media. Along with the essential need to examine current trends in Nazism and neo-Nazism in contemporary media globally, what makesthis book even more necessary is that it engages with debates that go to the very heart of our understanding of knowledge: history, memory, meaning, and truth.